Synthesis and Characterization of Rare Earth Complexes Containing Piperonal Dimethyl Acetal and Dicyclopentadienyl - Luo, Mei; Ma, Huai-Zhu; Su, Qing-De; Li, Qian-Rong; Hu, Nai-Liang (Asian Journal of Chemistry, 2010)
Five new organolanthanide complexes C20H21O4Ln (Ln : Yb, Dy, Pr, La, Sm) was synthesized by the reaction of anhydrous Cp2InCl with LiC10H11O4 in THF at low temperature, these complexes were characterized by elemental analysis, IR and MS.